It’s not (all) about the money — supporting IPBES through challenging times - Christian Hof; Marten Winter; Stefan Hotes; Lars Opgenoorth (Frontiers of Biogeography)
"An IPCC for biodiversity" – this is what many people were hoping for when the Intergovernmental Platform for Biodiversity and Ecosystem Services (IPBES) was founded. IPBES has had a very promising start – with a comprehensive conceptual framework and an ambitious work program. Its first published thematic assessment on pollinators, pollination and food production received wide attention within the scientific community and far beyond; the uptake by decision makers at national and regional levels has been impressive. However, during its last plenary session in March 2017, IPBES was confronted with difficult decisions due to insufficient financial pledges to the Platform’s Voluntary Trust Fund. Here, we discuss the potential consequences of the budget cuts as well as other challenges IPBES is facing, such as in facilitating stakeholder engagement. We encourage all biogeographers and other biodiversity scientists to engage in the IPBES process - to give IPBES a chance to flourish and thereby to give biodiversity an opportunity to remain on the global political agenda.